NK Cells Regulate CD8 T Cell-Mediated Allogeneic Rejection in Immunocompetent Recipients across an MHC Class I Mismatched Barrier. (July 2018) - Rodriguez-Barboza, Jose Ignacio; del Rio-Gonzalez, Maria Luisa; Ferreras, Maria Carmen; Buhler, Leo; Fernandez-Renedo, Carlos; Perez-Simon, Jose Antonio
Abstract : N/A: Non-T natural killer (NK) cells are a population of granular lymphoid cells TcR- CD3− CD122+ (NK1.1+ in C57BL/6 mice and DX5+ in Balb/c mice). These innate lymphoid cells mature in the bone marrow and are responsible for killing viral-infected and transformed cells in a non-MHC restricted manner, without the need of prior sensitization due to a recognition mechanism based on the array of germline-encoded inhibitory and activating receptors expressed on the cell surface of NK cells [1]. NK cells modulate CD8 T cell expansion during homeostatic proliferation in response to lymphopenic conditions by killing activated T cells and competing for IL-15 with the proliferating CD8 effector T cells [2]. This NK cell behavior may respond to an adaptive evolutionary mechanism to prevent aggressive anti-viral immune responses during the acute phase of infection and thus attenuate immunopathology [3]. We set up an experimental mouse model of alloreactivity across an MHC class I barrier to evaluate the role of NK cells in CD8 T cell-mediated rejection of bm1 skin allografts in naïve B6 recipients. In this transplant setting, host CD8 T cells are the main effectors T cells involved in the rejection of class I MHC mismatched skin allografts preferentially through the direct pathway of antigen presentation with limited help from CD4 T cells primed by the indirect pathway of antigen presentation. As opposed to previous studies done in lymphopenic immunodeficient recipients [2], depletion of NK cells was performed in immunocompetent C57BL/6 recipients with or without CD8 T depletion, the former displaying homeostatic proliferation in response to lymphopenia due to antibody-mediated elimination of CD8 T cells. We observed that depletion of NK cells in both CD8-repleted and CD8-depleted naïve C57BL/6 immunocompetent mice accelerated significantly bm1 graft rejection compared to non-NK-depleted controls (p<0.0005) (Figure 1). Our data claims for precaution in solid organ transplantation under inducing protocols of extensive depletion of leukocytes, such as ATG or alentuzumab. The immunotherapeutic interventions that include the removal of NK cells may accelerate graft rejection and promote aggressive CD8 T cell cytotoxic responses, which could be refractory to current immunosuppression. It also suggests that enhancing NK-cell functional activity combined with CD8 T cell depletion under tolerogenic regimen that tolerizes CD4 T cells at the time of transplantation may contribute to allogeneic donor-specific tolerance induction by elimination of the direct pathway of antigen presentation and by regulating the recovery of CD8 T cells. FIGURE 1. Host NK cells modulate the early phase of CD8 T cell alloreactive response in immunocompetent recipients. Left panel: Survival curve of bm1 skin grafts in non-depleted and NK-cell depleted B6 recipients. Depletion of NK cells significantly accelerated bm1 skin graft rejection in naïve C57BL6 mice compared to isotype control (***, p<0.0005). Right panel: Survival curve of bm1 skin grafts into C57BL/6mice in which depletion of NK cells in CD8 T cell depleted mice accelerated bm1 skin graft rejection compared to CD8 T-cell depletion only (***, p<0.0005). Bibliographic References: 1. Lanier LL. NK cell recognition. AnnuRevImmunol. 2005; 23: 225-74. 2. Zecher D, Li Q, Oberbarnscheidt MH, et al. NK cells delay allograft rejection in lymphopenic hosts by downregulating the homeostatic proliferation of CD8+ T cells. Journal of immunology (Baltimore, Md: 1950). 2010; 184: 6649-57. 3. Pallmer K, Oxenius A. Recognition and Regulation of T Cells by NK Cells. Frontiers in immunology. 2016; 7: 251. Consorcio CIBER-ONC. Acción Estrategica en Salud 2013-2016, Grant # CB16/12/00480. Acción Estrategica en Salud 2013-2016, Grant # PI16/00002. Consejería de Educación de la Comunidad de Castilla y León. Referencia: Grupos Consolidados de Investigación UIC-012. Referencia: LE003U16. GRS1505/A/17. Gerencia Regional de Salud de la Junta de Castilla y León.